Making a Logo as Destination Branding: Case Study Kebon Jayanti Ceramic Centre - I Kurniawan; R S Novanto (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Bandung is a city known for its various local wisdom and diverse cultures. Continuing to preserve the value of intergenerational traditions in the current of modernization. Among the various creative industries that Bandung has, there are communities that are trying to maintain the traditional pottery culture. The Kebon Jayanti ceramic centre is a center for pottery craftsmen in Bandung, which was inaugurated in 1960 by the Bandung City Government as a tourist spot for shopping for ornamental pottery. Its products have been marketed to all regions in Indonesia. Since its inception, the products of the Kebon Jayanti ceramic centre have continued to change in terms of form, function, and style due to changes in business owners. This condition is vulnerable to the identity of the producer which is difficult to identify. So that the brand from Kebon Jayanti ceramic centre is less well known, and also has an impact on its existence. The method used in this research is qualitative approach, revealing identity through the history, purpose, and role of craftsmen in the Kebon Jayanti pottery industry and then translated into a visual identity. This research produces a visual identity in the form of a logo that can be used to build the image of the Kebon Jayanti ceramic centre. The logo that has been designed is also applied to the media for supporting the brand image. Starting from stationery design, packaging, merchandise, and signage that can introduce, strengthen, and expand the reach of the Kebon Jayanti ceramic centre brand. Through this visual identity design, it is hoped that consumers can easily remember and identify the Kebon Jayanti as a ceramic center that has unique culture and is interesting to visit.